Efektivitas model conceptual understanding procedurs terhadap kemampuan berpikir kritis dalam pembelajaran matematika di SD kelas V - Niki Indiyasari (COLLASE (Creative of Learning Students Elementary Education), 2023)
This study aims to examine the effectiveness of the Conceptual Understanding Procedurs model on critical thinking skills in fifth grade mathematics learning. This study used an experimental research type. The research design uses experiments, the research design used is the Nonequivalent Control Group Design. This research was conducted in class V of SDN Dengkek 01 with 27 students, SDN Geritan with 31 students. The collection of data used is a test. Testing the hypothesis to be analyzed is using the Independent T-test and the N-Gain test. The research results obtained are : the Conceptual Understanding Procedures (CUPs) model is effective for students' critical thinking skills in mathematics in elementary mathematics learning.Keywords: CUPs, Critical Thinking AbilityÂ